2013
DOI: 10.1080/03601277.2012.703583
|View full text |Cite
|
Sign up to set email alerts
|

Older People Becoming Successful ICT Learners Over Time: Challenges and Strategies Through an Ethnographical Lens

Abstract: Older people becoming successful ICT learners over time: challenges and strategies through an ethnographical lens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 12 publications
(10 reference statements)
1
74
0
1
Order By: Relevance
“…This does not, of course, mean that innovative approaches should not be offered to older carers; more that emphasis needs to be on offering choice and being sensitive to changing contexts of care (Dickinson & Hill 2007, Scottish Government 2011b, Sayago et al 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This does not, of course, mean that innovative approaches should not be offered to older carers; more that emphasis needs to be on offering choice and being sensitive to changing contexts of care (Dickinson & Hill 2007, Scottish Government 2011b, Sayago et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Olsen et al 2011, Barnard et al 2013, Yagil et al 2013. Nevertheless, for many older people, ICTs (such as mobile phones, Internet banking and emails) are gradually becoming part of everyday life and, in the future, are likely to extend further into management of health and well-being (Dickinson & Hill 2007, Sayago et al 2013. Within the context of respite care, understanding how ICTs might best support information-sharing between carers, older people and respite staff is, therefore, potentially important.…”
Section: Introductionmentioning
confidence: 99%
“…Perceived benefit is a strong motivator for technology adoption at older ages [24], so a failure to understand social media’s potential benefits may inhibit its uptake [22, 25]. Social media are often considered a lesser form of interaction than more traditional communication forms [22, 26], so older adults may opt to engage in richer media, such as a telephone, to communicate with others.…”
Section: Older Adults and Social Mediamentioning
confidence: 99%
“…One ethnographic study of the learning strategies used to master technologies such as word processing and email found that older learners prefer learning collaboratively and informally. They also place a priority on taking their own notes over reading books or magazines, perhaps to compensate for perceived challenges such as age-related declines in fluid intelligence and memory [24]. Older adults also tend to orient their learning activities toward addressing real-life needs [24], underscoring the importance of perceived benefit in technology use.…”
Section: Older Adults and Social Mediamentioning
confidence: 99%
“…The studies targeting cognition models of technology use have provided different evidence for the influence of time on the relationship between ease of use and behavioural control where the influence can be expected to remain stable over time (e.g. Sayago et al, 2013). Perceived ease of use is related to familiarity and attitudes in this case, which results from the accumulation of expertise and the routines of using technology (Sun and Jeyaraj, 2013).…”
Section: Time Influence On Technology Perceptionsmentioning
confidence: 99%